PELAKSANAAN PROGRAM TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN DAARUL QUR’AN SRAGEN - Bin Auf Alamin, Fatahhillah Abdurrahman; Inayati, Nurul Latifatul (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
-Daarul Qur'an Sragen Islamic boarding school is a modern Islamic boarding school in the Sragen area which also presents the tahfidz Al-Qur'an program as the flagship program. The Al-Qur'an tahfidz program at the Daarul Qur'an Sragen Islamic boarding school targets students to 15 juz in three years. The purpose of this research is to find out about the implementation of the tahfidz Al-Qur'an program at the Daarul Qur'an Sragen Islamic Boarding School and to identify the supporting factors and obstacles to the implementation of the tahfidz program.This research belongs to the type of qualitative research which uses data collection techniques through observation, interviews, and documentation. The data analysis that has been obtained is done by using the deductive method. The analysis departs from general events and then is reduced to special parts.The Al-Qur'an tahfidz program at the Daarul Qur'an Sragen Islamic Boarding School is programmed for all students. The program targets the memorization of 15 juz within three years. The Al-Qur'an tahfidz program is carried out every day in three activities, namely after dawn, before maghrib, and after isha '. The evaluation of the tahfidz program consists of three types, namely daily assessments, tahfidz exams according to memorization targets, competition-style exams held before graduation. The supporting factors for the implementation of the Al-Qur'an tahfidz program are the intention and youth, the existence of prayers and support from parents, motivation from friends, the existence of rewards and punishments, and a supportive time and place as well as instructors who guide them well. And the inhibiting factors are laziness, boredom, and boredom of students due to routine. Besides, there are difficulties in managing time, programs implemented in one place for all halaqohs, and also social environmental factors, namely like to follow less orderly friends.